Reposição de corticoesteróides em crianças com choque séptico - Amoretti, Carolina Friedrich (2012)
Objectives: To evaluate hydrocortisone treatment and response to ACTH adrenal stimulation test, with or without respect to basal cortisol, in children with volume refractory septic shock.Method: Randomized placebo controlled clinical trial, including children admitted to the Pediatric Intensive Care Unit at São Lucas Hospital (HSL-PUCRS, Brazil) with a diagnosis of volume refractory septic shock, between Jun/2008 and Sep/2012. Basal cortisol level was determined and, then, ACTH test (1mcg/1,73m2) was performed. Then, patients were randomized to hydrocortisone or placebo treatment groups. Study protocol was approved by the HSL´s ethics committee.Results: Fifty six patients were analyzed. Median age was 5 months old, and mortality was 17.8%. Mortality rate was higher in patients that failed to respond to ACTH test, regardless of treatment (36% versus 6%; p=0.01). There was no difference between treatment groups regarding time and dose of vasoactive drugs, PICU length of stay and mortality, even when those who fail to respond to ACTH test were analyzed separately.Conclusion: Mortality was higher among patients who failed to respond to ACTH stimulation test, regardless of group of treatment. In our study, steroid replacement in children with volume refractory septic shock failed to improve mortality or any other studied outcome. More studies are needed to confirm these results